ChemInform Abstract: 25th Anniversary Article: Understanding the Lithiation of Silicon and Other Alloying Anodes for Lithium‐Ion Batteries. Issue 48 (26th November 2013) - McDowell, Matthew T.; Lee, Seok Woo; Nix, William D.; Cui, Yi
Abstract Review: 145 refs.